Deep-Contextual Teaching and Learning in Islamic Religious Education: Effects on Students’ Learning Outcomes - Nurfadhilah Nurfadhilah; Zainal Asril; Milya Sari; Rehani Rehani; Rivdya Eliza; Juliana Batubara; Musalwa Musalwa (STIT Ahlussunnah Bukittinggi, 2026)
This study is motivated by the condition of Islamic religious education learning in schools, which has not yet achieved its ideal outcomes. Ideally, successful learning should be reflected in students’ attitudes and behaviors in their daily lives, contributing to positive personal development. However, this condition has not been fully realized, as instruction is still often conducted using conventional approaches that limit student participation and hinder the achievement of learning objectives. Therefore, this study aims to develop and examine the effectiveness of a deep-contextual teaching and learning model in Islamic religious education at the junior high school level. This study employed a pre-experimental design using a one-group pretest and posttest approach with cluster random sampling. Data analysis was conducted using comparative statistical testing and gain score analysis to evaluate improvements in student learning outcomes. The findings indicate a significant difference between students’ performance before and after the implementation of the model, demonstrating a meaningful improvement in learning outcomes. The gain score analysis shows a moderate level of improvement, indicating that the model has a positive impact on student learning. The deep-contextual teaching and learning model is effective in improving learning outcomes in Islamic religious education at the junior high school level.